A methodological framework for crafting situated services. (15th September 2021) - Mazzarella, Francesco; May, Andrew; Mitchell, Val
Abstract : Purpose: This paper discusses how service design can be used to activate a transition of textile artisan communities towards a sustainable future. Design/methodology/approach: Two participatory case studies were undertaken with textile artisans in the UK and South Africa. These led to the development of an original methodological framework for "crafting situated services" – services designed to be meaningful to the local communities within which they are embedded. An evaluation study assessed the originality of the framework, its relevance for tackling real-world problems, its extensibility and the rigour of the research process. Findings: The framework brings together a variety of roles, methods and tools that designers can adopt in order to enter communities, make sense of sustainable futures, facilitate the co-design of situated services and activate legacies within communities. Building on emerging anthropological approaches, the framework makes a bridge between service management and service design for social innovation, advancing the field towards design for social entrepreneurship. Originality/value: Arguing against the idea of the designer "parachuting" into communities to create services regardless of the local context, the concept of "situated services" is proposed in this paper, alongside a process for "crafting" meaningful social innovations. This requires the service designer to adopt a more situated and embedded approach to designing with communities in order to align with their needs and aspirations, interweave places, time, people and practices within the process, and co-design contextually better services.